Determinants of Digital Banking Adoption Among Generation Z: The Role of Social Media and Influencers in Jakarta - Ameera Danish Arista; Zenal Asikin; Anggi Mayang Sari (School of Business, IPB University (SB-IPB), 2026)
Background: The rapid growth of digital banking in Indonesia is driven by increasing internet penetration and the widespread adoption of digital platforms, particularly among Generation Z. As digital natives, Generation Z relies heavily on social media and digital information sources, which play a crucial role in shaping their financial decision-making and adoption of digital banking services.Purpose: This study aims to analyze the role of social media and influencers in influencing Generation Z’s intention to use digital banking services, specifically SeaBank, in DKI Jakarta.Design/methodology/approach: A quantitative approach is employed using survey data collected from 100 Generation Z respondents. The data are analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships between social media, influencers, and intention to use digital banking.Findings/Result: The results indicate that social media has a positive and significant effect on intention to use digital banking, while influencers show a positive but statistically insignificant effect. These findings suggest that platform-based information exposure plays a more dominant role than individual endorsements in shaping behavioral intention.Conclusion: Digital banking adoption among Generation Z is primarily driven by the relevance, accessibility, and usefulness of information delivered through social media platforms rather than by influencer credibility alone. This reflects a shift toward platform-driven engagement in financial decision-making.Originality/value (State of the art): This study contributes to the literature by integrating social media and influencer variables within the Information Adoption Model (IAM) in the context of digital banking. It highlights the evolving role of digital information sources in financial behavior, particularly among Generation Z, and provides new insights into the relative effectiveness of platform-based versus influencer-based communication. Keywords:behavioral finance, digital banking adoption, Generation Z, intention to use, information adoption model